Analysis of the Conservative Energy Principle in Loop the Loop Trajectory on Roller Coasters - Awal Mulia Rejeki Tumanggor; Ishak Pawarangan; Berton Maruli Siahaan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2024)
The conservative energy principle is one of the fundamental concepts in physics used to understand closed mechanical systems. This research aims to analyze the application of the conservative energy principle through a qualitative approach in the loop trajectory on a simple roller coaster. The research method used is descriptive analysis, with information collected through literature study on the loop trajectory as well as concept analysis and formulation of study results. The analysis results explain that the law of conservative energy can explain how the mechanical energy in the system is maintained while going through the loop trajectory by reviewing important parameters such as normal force, minimum speed, radius of the loop trajectory, and minimum height.